Mendelisme dalam Oftalmogenetika - Hartono, Hartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
Mendelian disorders are genetic diseases caused by a mutant gene or a pair of mutant genes, either dominant or recessive, located in the autosomal or sex-chromosomes.The exact location of several genes in the chromosomes has been established by various rnethods. According to The Edinburgh Conference 1979 the location of 260 genes in the chromosomes has been identified.Based on the nature of the mutant genes (dominant or recessive) and the location of the mutant genes (in the autosomes or sex-chromosomes), Mendelian disorders may be transmitted by:a.autosomal dominant,b.autosomal recessive,c.X-linked dominant,d.X-linked recessive, ande. Y-linked mode of inheritance.Retinoblastoma, macular corneal dystrophies and color blindness are the examples of Mendelian disorders in ophthalmogenetics transmitted by autosomal dominant, autosomal recessive and X-linked recessive mode of inheritance respectively. In addition, a list of other Mendelian disorders affecting the eye have been presented.Key Words: Mendelian disorders - mutant genes - gene location - sex-linked mutant ophthalmogenetics